MEASUREMENT OF RETINAL NERVE FIBER LAYER THICKNESS IN PATIENTS OF UNILATERAL AMBLYOPIA USING OPTICAL COHERENCE TOMOGRAPHY - Munim, Abdul; Abbas, Sohaib; Ahmed, Arsalan; Sarfaraz, Sana Ahmed; Ikram, Rahela (Journal of Ayub Medical College Abbottabad, 2022)
Background: The retinal changes that develop in the eyes during amblyopia are still unclear. It has been proven that thickness of the nerve fiber layer of the retina is positively correlated with refractive error. The objective of the present study was to measure the Retinal Nerve Fiber Layer Thickness (RNFLT) using Ocular Coherence Tomography (OCT) in patients of amblyopia. Method: A descriptive study was conducted in the Department of LRBT Free Eye Hospital, Lahore for 6 months. After meeting the inclusion criteria, 80 patients (40 amblyopic and 40 normal) were taken and grouped as A and B. Socio-demographic details of all the patients were recorded. They then underwent a complete ophthalmologic evaluation that included BCVA, slit lamp biomicroscopy, OCT examination was carried by TOPCON OCT. Each examination was done using the fast retinal thickness protocol for each test eye. Mean RNFLT was calculated for each eye. Results: The mean age of patients was 12.58±4.44 years. There were 20 (50%) males and 20 (50%) females. In amblyopic eyes, the mean RNFLT was 125.82±13.06mm while in normal eyes, the mean RNFLT was 94.82±1.11mm. The overall mean RNFLT was significantly higher in amblyopic eyes as compared to normal eyes (p<0.01), as well as significant when data was stratified for age and gender. Conclusion: There was significant difference observed in RNFLT in amblyopic eyes as compared to normal eyes. So these results can help us to enhance our knowledge and understand the causes of amblyopia hence improving diagnosis and management of disease.